BERMAIN DALAM RANGKA MENGEMBANGKAN MOTORIK PADA ANAK USIA DINI - Lydia Ersta Kusumaningtyas (Universitas Muhammadiyah Ponorogo, 2016)
Outdoor playing emphasis on the development of gross motor coordination, namely the leg muscles, hands and body flexibility, while developing fine motor skills are usually carried out by playing in the room. By playingchildren can learn to explore, develop potential, and develop a curiosity and increase his confidence. The first five years of a child’s life is important to develop motor skill include gross and fine motor skill. What is interesting about this motor development can be separated whith a dynamic posture that will achieve movement and can be separated from environmental influences and the maturation of motor nerve system